2023
DOI: 10.1021/acsomega.3c02176
|View full text |Cite
|
Sign up to set email alerts
|

Pumpkin and Pumpkin Byproducts: Phytochemical Constitutes, Food Application and Health Benefits

Abstract: Nowadays, agricultural waste byproducts are exploited in the food industry rather than discarded. Pumpkin is one of the most significant vegetable crops that is widely consumed in farmland and certain urban regions. The current study was designed to measure the phytochemical constituents, food application, health benefits, and toxicity of pumpkin and pumpkin byproducts. Pumpkins and pumpkin byproducts (seeds, leaf, and skin/peel) can be utilized as functional ingredients. Different parts of the pumpkin contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…is a species belonging to the cucurbitaceae family. Pumpkins and pumpkin byproducts (seeds, leaf, and skin/peel) are widely used as functional foods by people because of their various bioactive compounds, including Selenium (Se) (Aziz et al, 2023). Se is thought as an indispensable metalloid element for animals and humans (Tangjaidee et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…is a species belonging to the cucurbitaceae family. Pumpkins and pumpkin byproducts (seeds, leaf, and skin/peel) are widely used as functional foods by people because of their various bioactive compounds, including Selenium (Se) (Aziz et al, 2023). Se is thought as an indispensable metalloid element for animals and humans (Tangjaidee et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Various investigations have been conducted across the globe on several varieties of pumpkin seeds, particularly C. pepo, C. moschata, and C. maxima. It has been claimed that pumpkin seeds contain anti-diabetic, antimicrobial, antioxidant, anti-inflammatory, anti-cancer, anti-tumor, antimutagenic, and antiulcer effects (Aziz et al, 2023;Sharma et al, 2020). Pumpkin seeds are high in protein, fat, antioxidants, fiber, phytochemicals, and vitamins, rendering them an excellent source of nourishment (Agrawal and Shahani, 2021;Hussain et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…Effects of butternut fibres acquired from C. moschata on bread production was studied and reported that adding fiber ranging from 5 to 15 grams to 1 kilogram wheat flour can be promising to enhance the structure of the bread following baking process and through storage (de Escalada Pla et al, 2013). Aziz et al (2023) stated that pumpkin flour might also promote the way of gluten working in the dough such as assisting the rise of the bread and stabilization of the gas cell texture.…”
Section: Introductionmentioning
confidence: 99%